Metodologia de projeto de conversores boost para correção de fator de potência apliocada a sistemas ininterruptos de energia - Damasceno, Daniel da Motta Souto (2006)
This Master Thesis presents a design methodology to a boost PFC converter operating as an Uninterruptible Power Supply rectifier input stage. This methodology defines, making use of a group of current ripples and switching frequencies, the converter minimum volume point analyzing the volumes of the boost inductor, the electromagnetic interference filter and the heat-sinks. Thus, it's developed along this work, each design mentioned above, analyzing the impact of different magnetic materiaIs, input filter topologies and semiconductors technologies. Previously, it is designed the controller and it is developed a simulation structure. ln a second moment, it's designed the boost inductor for a predetermined temperature elevation. After this, it's designed the electromagnetic filter analyzing the impact of different topologies. The heat-sinks are also designed to guarantee the semiconductors operation within the temperature limits. Finally, the methodology based on the previous designs is accomplished, using the procedures and equations already mentioned, becoming possible to define the converter minimum volume point.